Разложите на множители a(b - c) - (c - b) (a - 1)(b - c)
(a + 1)(b - c)
(a - 1)(c - b)
(a + 1)(c - b)

Алексей000999 Алексей000999    2   30.10.2020 14:16    0

Ответы
chhfyf chhfyf  29.11.2020 14:17

a(b - c) - (c - b)=a(b - c) + ( b-c)=(a+1)(b-c)

ПОКАЗАТЬ ОТВЕТЫ
katerina17054 katerina17054  29.11.2020 14:17

a(b-c)-(c-b)=a×(b-c)-(-(b-c))=a×(b-c)+(b-c)=(b-c)×(a+1)

(a-1)(b-c)=ab-ac-b-1×(-c)=ab-ac-b+1c=ab-ac-b+c

(a+1)(b-c)=ab-ac+b-c

(a-1)(c-b)=ac-ab-c-1×(-b)=ac-ab-c+1b=ac-ab-c+b

(a+1)(c-b)=ac-ab+c-b

Если неправильно, то извините

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра